Analisis Profitabilitas Bank Umum Persero yang Terdaftar di OJK Ditinjau dari CAR, NPL, NIM, LDR, dan BOPO Periode Tahun 2016-2020 - Laily Ummayatul Aprilia Sari; Heri Prabowo; Bayu Kurniawan (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2022)
This study was conducted with the aim of analyzing the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and Operating Costs on Operating Income (BOPO) on Profitability of Commercial Banks. Persero period 2016-2020. The data used in this study were obtained from the published financial statements of Persero Commercial Banks issued by the Financial Services Authority (OJK). After doing the purpose sampling stage, 4 banks were obtained that were suitable for use. The data analysis technique in this study used multiple linear regression analysis, but before testing the hypothesis, the classical assumption test was first carried out. The test results using the t test showed that the variables CAR, NPL, LDR had no effect on bank profitability, NIM had a positive and significant effect on bank profitability, and BOPO had a negative and significant effect on bank profitability.